2001
DOI: 10.1089/109264201750539682
|View full text |Cite
|
Sign up to set email alerts
|

How Do Bile Duct Injuries Sustained During Laparoscopic Cholecystectomy Differ from Those During Open Cholecystectomy?

Abstract: Compared with open cholecystectomy, biliary injuries sustained during laparoscopic cholecystectomy are more likely to present earlier, are more often associated with persistent bile leaks, and are usually high injuries. However, the results of surgical repair do not appear to be different in these two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 18 publications
5
24
1
1
Order By: Relevance
“…In our observation, type A injury was more common with laparoscopic cholecystectomy whereas type E3 was more common with open cholecystectomy. This contradicts the earlier observation that laparoscopic surgery is associated with severe and more complex BDI [10,11].…”
Section: Discussioncontrasting
confidence: 90%
“…In our observation, type A injury was more common with laparoscopic cholecystectomy whereas type E3 was more common with open cholecystectomy. This contradicts the earlier observation that laparoscopic surgery is associated with severe and more complex BDI [10,11].…”
Section: Discussioncontrasting
confidence: 90%
“…In one of the first major multicentre trials Woods et al reported approximately 37% of injuries diagnosed intra-operatively when an IOC was not performed. Walsh, Lillemoe and Chaudhary and their co-workers had 29%-30% intra-operatively diagnosed lesions in their series [72,83,87], while Richardson stated that less than 50% are diagnosed intra-operatively [3]. However, this is a major problem in the management of bile duct injuries because it is a matter of fact that, beside the surgeons experience [88], early diagnosis improves the results [63,89].…”
Section: Diagnosis and Managementmentioning
confidence: 99%
“…The use of IOC is still controversial, and opinions are split between routine 1,2,3 and selective use. 4 Nevertheless, the incidence of CBD stones is approximately 3.3%, 5 and the detection rate of CBD abnormalities or injuries intraoperatively is reported in the range of 18 to 37%, 6,7,8 suggesting that biliary complications might be detected earlier and more frequently with its routine use. 6 In addition, early diagnosis of stones and injuries is reported to improve treatment outcome.…”
Section: Introductionmentioning
confidence: 99%